2016
DOI: 10.1159/000443216
|View full text |Cite
|
Sign up to set email alerts
|

Non-Steroidal Anti-Inflammatory Drug Use and Risk of Anastomotic Leakage after Anterior Resection: A Protocol-Based Study

Abstract: Background: Non-steroidal anti-inflammatory drugs (NSAIDs) have been introduced as opioid-sparing analgesics in colorectal surgery. However, recent research has implicated these drugs as risk factors for anastomotic dehiscence. Methods: The Swedish Colorectal Cancer Registry was used to identify all patients operated with anterior resection for rectal cancer at centres that performed more than 25 abdominal operations per year, from 2007 to 2012, inclusive. The registry provided individual patient data on demog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 29 publications
2
19
0
2
Order By: Relevance
“…29 In another large cohort study, patients enrolled in the Swedish Colorectal Cancer Registry were not at risk of anastomotic leak after the perioperative administration of NSAIDs for rectal cancer surgery. 28 In agreement with that investigation, Karlsson and colleagues 32 showed no association between the use of NSAIDs and anastomotic leaks after rectal cancer surgery. The impact of NSAIDs use on anastomotic leak has also been investigated in upper gastrointestinal cancers.…”
Section: Perioperative Nsaids and Anastomostic Leaksmentioning
confidence: 55%
“…29 In another large cohort study, patients enrolled in the Swedish Colorectal Cancer Registry were not at risk of anastomotic leak after the perioperative administration of NSAIDs for rectal cancer surgery. 28 In agreement with that investigation, Karlsson and colleagues 32 showed no association between the use of NSAIDs and anastomotic leaks after rectal cancer surgery. The impact of NSAIDs use on anastomotic leak has also been investigated in upper gastrointestinal cancers.…”
Section: Perioperative Nsaids and Anastomostic Leaksmentioning
confidence: 55%
“…The expertise of individual surgeons and preference regarding NSAID use, which might be confounders, were not considered. However, a previous study 23 from some of the centres involved in the present analysis suggested that NSAID use is largely driven by postoperative care protocols at each hospital, not by the surgeon; thus, this potential influence is likely to be negated. Although the exposure was assessed carefully using chart review, the outcome data for recurrence were derived only from registry data.…”
Section: Discussionmentioning
confidence: 82%
“…Interestingly, Yauw and co-workers 40 recently showed that diclofenac, a commonly used NSAID, caused AL in the ileum and proximal colon, but not in the distal colon. Furthermore, more recently, Rutegård et al 41 found no increased risk of AL with NSAID use in patients undergoing anterior resection for rectal cancer. Previous associations between AL and NSAIDs were derived from pooled data for colorectal surgery, not solely rectal resections.…”
Section: Discussionmentioning
confidence: 98%